Determinants of family physicians' workland - Živčec-Kalan, Gordana (Zdravniški vestnik, 2012)
Methods: We performed a nationwide cross sectional study on a representative sample of 50 randomly selected family physicians in Slovenia; 41 out of 50, each collecting data from 300 consecutive encounters, participated in the study. We collected data from 12,297 office contacts and home visits. The workload was defined with activities and with a stopwatch-measured time spent during consultations with/for patients by a family physician on a typical working day. We analysed patientsć characteristics, physiciansć style of work and the influence of the working environment. Results: Practices differed 3.70times in the number of patients on the list, 3.84 times in population points, 2.44 times in average age of patients on the list and 2.51 times in the number of doctor-patient encounters per day. We calculated 1.97 time differences (from 0.67 to 1.32) in mean workload. The mean time used for direct work with patients per day was 390.04 minutes (min. 261.22 min, max. 516.67 min, SD 65.18 minutes). The highest impact on the length of work had visits with (p = 0.002) or without (p < 0.001) physical examination and performing medical procedures (p = 0.019) due to their frequency as well as home visits (p = 0.001) and performing coroner duties (p = 0.038) due to the length of time in delivering them. Conclusions: Our observations can be used to develop a model for predicting and/or planning family physiciansć workload in the Slovenian health care system. The model needs to be tested in other countries with a similar (capitation combined with fee for service) payment system in order to determine its universal applicability.
Keywords: ankete; Cross-Sectional Studies; Časovni faktorji; Delovne naloge; Delovno mesto; Družinska medicina; Family Practice; Physician-Patient Relations; Presečne študije; Questionnaires; Time Factors; Workload; Workplace; Zdravnik-bolnik, odnosi